Early-onset neonatal sepsis caused by Neisseria meningitidis serogroup B: case report and literature review of a 102-year period - Mubashar, Tayyib; Turner, Paul Christopher; Paul, Siba Prosad (The Turkish Journal of Pediatrics, 2020)
A 36-week-2-day-old male infant was admitted to the neonatal unit with respiratory distress, hypoglycaemia and suspected early onset neonatal sepsis for respiratory support, monitoring and intravenous antibiotics. His initial C-reactive protein was 12 mg/L, this increased to 66 mg/L at 24 hours. Blood cultures at 48 hours confirmed Neisseria meningitidis serogroup B. As the isolate was sensitive to benzylpenicillin the same antibiotic was continued for a total of 7 days. His mother remained asymptomatic but was monitored closely. Ciprofloxacin chemoprophylaxis was given to close family contacts. Neisseria meningitidis causing early onset neonatal sepsis is extremely rare and neonates may have minimal symptoms at presentation. A table reviewing all documented cases of early onset neonatal sepsis caused by Neisseria meningitidis over a 102-year time period is included. There is need for early identification and initiation of empirical antibiotic therapy pending confirmation and sensitivities.
Keywords: Neisseria meningitidis; antibiotics; chemoprophylaxis; invasive meningococcal disease; neonatal sepsis